Relationship between quality of life (QoL) and academic performance during e-learning among students in higher learning institution - Mohd Helmi Razali,; Wan Zaiton Wan Sulaiman,; Noor Diana Abdul Majid,; Nurliyana Moh Hussin,; Azizan Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The level of education and academic performance at the Universiti Malaysia Pahang (UMP) depends on having a better understanding of the standard of living among students there. The study aims to acquire the relationship between psychological, social, and environmental conditions and academic performance during e-learning among students from Universiti Malaysia Pahang, Gambang. This study aims to ascertain the relationship between the variables affecting students' performances and their outcomes in UMP, Gambang. Data were collected from 326 students through a questionnaire survey. The data were analysed using Statistical Package for the Social Sciences (SSPS) version 26 software. This study analysed three aspects that influence students' academic performance toward psychological, social, and environmental. The findings show that none of the hypotheses proposed are statistically significant for this study. The analysis result shows that psychological with a spearman-value of -0.043. Spearman-value of -0.097, and for social and environmental with spearman-value of -0.087. The results from this study reveal that all the listed factors have a weak contribution to the student’ academic performance.